Potential and Barriers to Development in Atule'er Village - Styawati, Endah; Kristy, Abelia (Journal of Maobi, 2023)
Tourist villages, in general, are rural areas with several characteristics worthy of being used as tourist destinations. It has several supporting factors, such as a unique location, unique accessibility to the village and a socio-economic system that also colours the tourist village. The village with steep stairs leading to the sky in the Daliang Mountains, Atule'er Village, Sichuan Province, China, is known as "Cliff Village". There are 2,556 steps to enter the village. Some areas have slopes of almost 90 degrees. The harvest is abundant, but it cannot be transported out due to the difficulty of access to the outside, which requires climbing down a cliff, and transportation still needs to be improved. This research aims to determine the development potential and obstacles of Atule'er Village in Sichuan Province, China. Apart from that, it also seeks to discover the challenges faced in the development process of Atule'er Village. The method used in this research is qualitative, utilizing literary sources such as books, journals and relevant related materials, which are used to collect data about the development potential and obstacles faced by Atule'er Village, Sichuan Province, China. The research results concluded that Atule'er Village, or what is usually called "Cliff Village", is a unique tourist village located around 800 meters above ground level, with a million good and bad stories and continues to grow to become "Tebing Village". "This has been talked about a lot and even become famous.